Limits of Responsibility: Genome Editing, Asilomar, and the Politics of Deliberation - Hurlbut, J. Benjamin (The Hastings Center report, 2015)
On April 3, 2015, a group of prominent biologists and ethicists called for a worldwide moratorium on human genetic engineering in which the genetic modifications would be passed on to future generations. Describing themselves as “interested stakeholders,” the group held a retreat in Napa, California, in January to “initiate an informed discussion” of CRISPR/Cas9 genome engineering technology, which could enable high-precision insertion, deletion, and recoding of genes in human eggs, sperm, and embryos. The group declared that the advent of a technology that makes human germ-line genetic engineering plausible makes a corollary discussion of its ethical implications urgent. Echoing this sentiment, the National Academy of Sciences and the National Academy of Medicine have announced plans to convene an international summit in fall 2015 to assess the implications of CRISPR/Cas9. Yet the notion that the advent of this particular technology is the warrant for initiating a public discussion is remarkable, and so too is the idea that the experts who have brought it into being and are putting it to use are best positioned to define the terms of the debate. The relevant ethical questions are by no means specific, let alone subsidiary, to the CRISPR/Cas9 technology. They are longstanding questions about what features of human life ought not be taken as objects of manipulation and control. They are questions about our responsibilities to our children and our children's children, where the mark of our actions will be inscribed upon their bodies and their lives.